A difficult‐to‐diagnose case of Borrmann type IV gastric cancer with marked transverse colon stenosis. Issue 11 (20th October 2022) - Natsui, Kazuki; Maruyama, Masaki; Terai, Shuji
Abstract: We report a difficult‐to‐diagnose case of Borrmann type IV gastric cancer with poor typical findings and marked colonic stenosis in a 47‐year‐old man and present a literature review. Abstract : We report a difficult‐to‐diagnose case of Borrmann type IV gastric cancer with poor typical findings and marked colonic stenosis in a 47‐year‐old man and present a literature review.